2015
DOI: 10.1002/2015rs005793
|View full text |Cite
|
Sign up to set email alerts
|

Channel characterization in high‐speed railway station environments at 1.89 GHz

Abstract: (2015) 'Channel characterization in high-speed railway station environments at 1.89GHz.', Radio science., 50 (11). pp. 1176-1186. Further information on publisher's website: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…e Ricean K-factor is defined as the ratio of the power of the strongest MPC to the power of the sum of the remaining MPCs in the received signal [40]. Traditionally, the Ricean K-factor is calculated from the narrowband channel sounding results by using a moment-based method [41]. However, the ultra-wideband (UWB) channel sounding results in this measurement have high resolution in the time domain.…”
Section: Rms Ds and Ricean K-factormentioning
confidence: 99%
“…e Ricean K-factor is defined as the ratio of the power of the strongest MPC to the power of the sum of the remaining MPCs in the received signal [40]. Traditionally, the Ricean K-factor is calculated from the narrowband channel sounding results by using a moment-based method [41]. However, the ultra-wideband (UWB) channel sounding results in this measurement have high resolution in the time domain.…”
Section: Rms Ds and Ricean K-factormentioning
confidence: 99%
“…There were also a few results of K-factor, RMS delay spread (DS), and Doppler power spectral density (DPSD) measured in the hilly terrain and tunnel scenarios [20][21][22]. Authors in [23,24] presented detailed analysis of fading severity and time dispersion in open-type and semiclosed station scenarios. For the nonstationary behavior, stationarity interval (SI) in the viaduct scenario was investigated based on GSM-R measurements, which showed that conventional channel models offered SI much larger than the actual measured ones [25].…”
Section: Related Workmentioning
confidence: 99%
“…For the nonstationary behavior, stationarity interval (SI) in the viaduct scenario was investigated based on GSM-R measurements, which showed that conventional channel models offered SI much larger than the actual measured ones [25]. We also tried to adopt a RUN test method to obtain the SI for the open-type station scenario in [24]. Additionally, a four-state Markov chain was used to model the birth-death (B-D) process of MPCs in the viaduct scenario [26].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The small-scale fading behavior, which is defined as signal variations occurring within very short distances, has been discussed in large numbers of papers for broadband mobile communications. Several wireless channel propagation measurement activities have been performed in different kinds of HSR scenarios, such as the train station [11][12][13], the viaduct [14][15][16][17], the cutting [18,19], the crossing bridge [20], the railway tunnel [21], the subway tunnel [22,23], and the passageway tunnel [24]. The empirical path loss model and small-scale fading parameters have been obtained at 930 MHz.…”
Section: Introductionmentioning
confidence: 99%